A novel mouse model of human prostate cancer to study intraprostatic tumor growth and the development of lymph node metastases. Issue 9 (24th March 2018) - Linxweiler, Johannes; Körbel, Christina; Müller, Andreas; Hammer, Markus; Veith, Christian; Bohle, Rainer M.; Stöckle, Michael; Junker, Kerstin; Menger, Michael D.; Saar, Matthias
Abstract : Background: In this study, we aimed to establish a versatile in vivo model of prostate cancer, which adequately mimics intraprostatic tumor growth, and the natural routes of metastatic spread. In addition, we analyzed the capability of high‐resolution ultrasonography (hrUS), in vivo micro‐CT (μCT), and 9.4T MRI to monitor tumor growth and the development of lymph node metastases. Methods: A total of 5 × 10 5 VCaP cells or 5 × 10 5 cells of LuCaP136‐ or LuCaP147 spheroids were injected into the prostate of male CB17‐SCID mice ( n = 8 for each cell type). During 12 weeks of follow‐up, orthotopic tumor growth, and metastatic spread were monitored by repetitive serum‐PSA measurements and imaging studies including hrUS, μCT, and 9.4T MRI. At autopsy, primary tumors and metastases were harvested and examined by histology and immunohistochemistry (CK5, CK8, AMACR, AR, Ki67, ERG, and PSA). From imaging results and PSA‐measurements, tumor volume doubling time, tumor‐specific growth rate, and PSA‐density were calculated. Results: All 24 mice developed orthotopic tumors. The tumor growth could be reliably monitored by a combination of hrUS, μCT, MRI, and serum‐PSA measurements. In most animals, lymph node metastases could be detected after 12 weeks, which could also be well visualized by hrUS, and MRI. Immunohistochemistry showed positive signals for CK8, AMACR, and AR in all xenograft types. CK5 was negative in VCaP‐ and focally positive in LuCaP136‐ and LuCaP147‐xenografts. ERG was positive in VCaP‐ and negative in LuCaP136‐ and LuCaP147‐xenografts. Tumor volume doubling times and tumor‐specific growth rates were 21.2 days and 3.9 %/day for VCaP‐, 27.6 days and 3.1 %/day for LuCaP136‐ and 16.2 days and 4.5 %/day for LuCaP147‐xenografts, respectively. PSA‐densities were 433.9 ng/mL per milliliter tumor for VCaP‐, 6.5 ng/mL per milliliter tumor for LuCaP136‐, and 11.2 ng/mL per milliliter tumor for LuCaP147‐xenografts. Conclusions: By using different monolayer and 3D spheroid cell cultures in an orthotopic xenograft model, we established an innovative, versatile in vivo model of prostate cancer, which enables the study of both intraprostatic tumor growth as well as metastatic spread to regional lymph nodes. HrUS and MRI are feasible tools to monitor tumor growth and the development of lymph node metastases while these cannot be visualized by μCT.